IJCM_257A: Effect of quality of sleep on anxiety and cognitive functions in medical students - Darshan B B; Chawla Sanchita; Stephen Jacob; Chandila Rupesh; Jose Joyel (Wolters Kluwer Medknow Publications, 2024)
Background: In human life, periods of activity and rest alternate. To survive, human beings need to work and every day properly we need sleep. The quality of sleep strongly influences psychological and physical health and other measures of well-being. Methodology: This was a cross-sectional study done in Kasturba Medical College, Mangalore among 300 medical undergraduate students using a questionnaire that consisted of general participant information and PSQI to assess the quality of sleep, GAD-7 scale to assess the level of anxiety, need for cognition scale. The results were expressed in the form of tables and graphs using SPSS V 25.0. The association between quality of sleep and anxiety was analyzed by using the Chi-square test and a p-value <0.05 was considered statistically significant. Results: Out of the total 300 students, 106(35.5%) of the students had good quality sleep,112(37.3%) of them had minimal anxiety, 92(30.7%) had mild anxiety,57(19%) had severe anxiety and 39(13%) had moderate anxiety. It was seen that there is an increased number of students with mild, moderate, and severe anxiety among poor-quality sleepers than those with good-quality sleep. Conclusion: Most of the medical undergraduate students have poor- quality sleep. Students with poor-quality sleep have increased anxiety levels compared to those with good-quality sleep. The cognitive function in students with poor quality of sleep is found to be higher than those with good-quality sleep.